The relationship between meniscal pathologies, cartilage loss, joint replacement and pain in knee osteoarthritis: a systematic review. Issue 10 (October 2022) - Ghouri, A.; Muzumdar, S.; Barr, A.J.; Robinson, E.; Murdoch, C.; Kingsbury, S.R.; Conaghan, P.G.
Summary: Objective: We conducted a systematic review in order to understand the relationship between imaging-visualised meniscus pathologies, hyaline cartilage, joint replacement and pain in knee osteoarthritis (OA). Design: A search of the Medline, Excerpta Medica database (EMBASE) and Cochrane library databases was performed for original publications reporting association between imaging-detected meniscal pathology (extrusion or tear/damage) and longitudinal and cross-sectional assessments of hyaline articular cartilage loss [assessed on magnetic resonance imaging (MRI)], incident joint replacement and pain (longitudinal and cross-sectional) in knee OA. Each association was qualitatively characterised by a synthesis of data from each analysis, based upon study design and quality scoring (including risk of bias assessment and adequacy of covariate adjustment using Cochrane recommended methodology). Results: In total 4, 878 abstracts were screened and 82 publications were included (comprising 72 longitudinal analyses and 49 cross-sectional). Using high quality, well-adjusted data, meniscal extrusion and meniscal tear/damage were associated with longitudinal progression of cartilage loss, cross-sectional cartilage loss severity and joint replacement, independently of age, sex and body mass index (BMI). Medial and lateral meniscal tears were associated with cartilage loss when they occurred in the body and posterior horns, but not the anterior horns. There was a lack of high quality, well-adjusted meniscal pathology and pain publications and no clear independent association between meniscal extrusion or tear/damage with pain severity, progression in pain or incident frequent knee symptoms. Conclusion: Meniscal features have strong associations with cartilage loss and joint replacement in knee OA, but weak associations with knee pain. Systematic review PROSPERO registration number: CRD 42020210910